Denoising of Laser Scanning Data Using Wavelet - Petr Jašek (Geoinformatics FCE CTU, 2014)
Regarding the terrestrial laser scanning accuracy, one of the main problems is the noisein measured distance which is necessary for the spatial coordinates ́ determination. In thispaper the technique of using the wavelet transformation for the reduction of the noise inthe laser scanning data is described. This method of filtration is made in “post processing”and due to this fact any changes in the measuring procedure in the field shouldn ́t be done.The creation of the regular matrix is needed to apply image processing. This matrix thenmakes the range image. In the paper real and simulated efficiency tests of wavelettransformation, the final summary and advantages or disadvantages of this method areintroduced.